Answer:
x = 0
Explanation:
First, distribute
- 2 (5x - 4) = 8 - 3x
-10x + 8 = 8 - 3x
Next, rearrange the terms
-10x + 8 = 8 - 3x
-10x + 8 = -3x + 8
Then, Subtract 8 from both sides of the equation
-10x + 8 = -3x + 8
-10x + 8 - 8 = -3x + 8 -8
Then, simplify (I'm not gonna show how but if you want me to just let me know)
-10x = -3x
Then, add 3x to both sides of the equation
-10x = -3x
-10x + -3x = -3x + 3x
Then, simplify
-7x = 0
Then, divide both sides of the equation by the same term
-7x = 0
-7x/-7 = 0/-7
Finally, simplify
x = 0/-7
and you'll get
x = 0